Pandemic experiences: views of the pedagogical experiences in the Bachelor of Early Childhood Education (FHUC-UNL) - Odetti, Cecilia Ángela (Universidad Nacional del Litoral, 2022)
The main goal of this work is to share pedagogical experiences in pandemic times developed in the framework of the Bachelor's Degree in Early Childhood Education (FHUC-UNL, Argentina) viewed by both perspectives: students of the degree and first level teachers. Experiences are recovered first of all as students, to stage the transition from face-to-face to virtual interactions with work in virtual classrooms and the implications of being on the screen as another way of meeting. The obstacles and possibilities that were generated from March 2020 are presented in this investigation. As teachers, on the other hand, the discussions are about experiences on education with young children, the situations they went through and the institutional decisions of which they were part to put in tension the importance of the commitment of the teacher and the families in the face of the various situations experienced by the pandemic.